(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Food safety remains a global public health concern, and the eruption of diseases caused by food contamination occurs in places where sanitation and hygiene conditions are generally poor. This study evaluated the microbiological quality and safety of ready-to-eat foods (Awara, Akara, and Masa) sold around Sa’adu Zungur University, Gadau Campus, Bauchi, Nigeria. A total of 27 samples were randomly collected from the cafeteria, Gadau Market, and off-campus sites over one month. Samples were immediately analyzed using standard microbiological assays, including serial dilution, inoculation, incubation, microscopy, and biochemical tests to identify and confirm microbial contaminants. A total of four pathogenic bacteria were isolated: Staphylococcus aureus (51.9 %), Escherichia coli (25.9 %), Salmonella species (18.5 %), and Pseudomonas species (3.7 %). Awara sample had the highest total aerobic bacteria count of 9.33 ± 0.37 x 105 cfu/g, with total coliform count (TCC) obtained ranging from 4.07 ± 2.8 x 105 to 7.20 ± 0.23 x 105 cfu/g. Akara sample has the highest TCC (7.20 ± 0.23 x105 cfu/g), and Staphylococcus count (TSC) of 5.40 ± 0.31 x 105 cfu/g, while Masa samples have the lowest TSC of 1.13 ± 0.03 x 105 cfu/g. The findings reveal poor hygiene among food vendors, likely due to inadequate food safety knowledge, posing health risks. Mandatory health certification, regular renewal, and food hygiene training are recommended to enhance safety and protect consumer health.